RESPONS ANAKAN TUMBUHAN NYAMPLUNG (Calophyllum inophyllum L.) PADA BERBAGAI PERIODE PENGGENANGAN - Asma Sari; Siti Fatonah; Dyah Iriani (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Nyamplung (Calophyllum inophyllum L.) is a plant that has many functions, almost all parts of the plant can be used and have high economical and ecological functions.The purpose of this study were to test the growth ability of nyamplung at various periods of flooding and observe the morphological adaptations due to this treatments.This research was carried out for 30 days using a randomized block design (RBD) with a single factor, i.e. period of flooding which consisted of 4 treatments as follow P0: control (no flooding), P1 5 days of flooding periods, P2 10 days of flooding periods, and P3 continuous floding. The flood height from the soil was 2 cm. The results of this study indicated that the flooding periods did not significantly affect the plant fresh weight, the plant height as well as the number of leaves.The flooding periods significantly affected the percentage of root growth and root fresh weight. The morphological adaptation of Nyamplung in the period of flooding was by forming lenticels.While the seedling on continuously flooding treatment also formed adventitious roots. The 4 month nyamplung seedling could grow at all of the flooding periods with injury index at 5, 10 day flooding periods and continuously flooding period were 0, 0.09 and 0.58, respectively.